Effects of salt concentration on the polyelectrolyte translocation through a cylinder nanopore. (December 2019) - Wang, Chang-Hui; Luo, Meng-Bo; Xu, Xiaojun; Wang, Chao; Sun, Li-Zhen
Graphical abstract: Highlights: Salt-induced screening effect on polyelectrolyte charges plays an important role in polyelectrolyte translocation. Electrostatic repulsion imbalance occurs for the sub-chain inside the pore in translocation process. The translocation time decreases with the increase in salt concentration. Salt concentration can change the scaling relation between translocation time and external driving force. The scaling relation between translocation time and chain length is held in various salt concentrations. Abstract: The salt concentration-dependent polyelectrolyte translocation through a cylinder nanopore is studied using Langevin dynamics simulation. We use the Debye-Hückel model combined with the generalized Born model to account for the salt-induced screening effect and the polarization effect for the polyelectrolyte charges. We prove the validity of our simulation model through the extensive simulation-experiment comparisons for the polyelectrolyte statistical size (the radius of gyration) at different salt bulk concentrations [s]. The simulation results show that the translocation time τ decreases with increasing [s]. At dilute [s], we find a power-law relation τ ~ [s] β with β < 0. The value of the exponent β is dependent on the driving force f but is insensitive to the polyelectrolyte length N . Moreover, we also study two important scaling relations τ ~  f δ (δ < 0) and τ ~  N α (α > 0) at different [s]. With the increase of [s], the exponent δ increases and approaches to −1 at high [s], while the exponent α is independent of the salt concentration no matter whether in the quasi-equilibrium state (α = 1.07) or in the non-equilibrium state (α = 1.35).